Intersectoral policy approaches to healthy cities with a focus on built and food environments - Weimann, Amy (Department of Public Health and Family Medicine, 2022)
Rapid urbanisation in many low- and middle-income countries in Africa has led to substantial changes in both built and food environments, with resultant changes to housing and diet, respectively. These changes interact with factors that influence risk of disease and healthcare access, and may contribute to, and exacerbate, inequities in health outcomes. Increasing global attention is given to the link between characteristics of built and food environments and health. In addition, international health agendas are calling for intersectoral action, which may be guided by the World Health Organization's Health-in-All-Policies approach, to address the social determinants of health that largely lie outside the reach of the health sector. The thesis uses two lenses to investigate the intersectoral determinants of health exploring: i) non-communicable diseases through a food environment lens in the African region, and ii) infectious diseases through a human settlement built environment lens in South Africa. Firstly, this research investigates the landscape of global, regional (African) and national (South African) policies to identify opportunities to integrate health considerations into diet-related and human settlements policies. Secondly, focusing on the built environment context of Cape Town, South Africa, this thesis provides a practical demonstration of a transdisciplinary research approach to gathering evidence, integrating data from health and non-health sectors, and building support for a future implementation of a Health-in-All-Policies approach within a sub-national government setting. In addition, an improved transdisciplinary research approach was developed to support future efforts to address health inequities through urban planning interventions.